Prototypische und essentialisierte Darstellungen von Religionen bei Jugendlichen - eine explorative Studie nach dem Modell der Didaktischen Rekonstruktion - Schellenberg, Urs (Zeitschrift für Religionskunde, 2019)
In an exploratory study, the preconceptions of two Year 8 secondary classes relating to Judaism were collected. The students showed extensive declarative knowledge but presented a homogeneous, stereotyped image of Judaism. Using the model of didactic reconstruction, the teaching was shaped so as to expand this conception through those of plurality and internal diversity. The results show on the one hand how difficult it is to change essentialist and prototypical conceptions of religion and on the other some important approaches to achieve this aim.